Active 6-D position-pose estimation of a spatial circle using monocular eye-in-hand system. (19th January 2018) - Ma, Xin; Feng, Junbing; Li, Yibin; Tan, Jindong
Nuts and bolts are common components in assembly lines. Their position and pose estimation is a vital step for automatic assembling. Although many approaches using a monocular camera have been proposed, few works consider a monocular camera's active movements for improving estimation accuracy. This article presents an active movement strategy for a monocular eye-in-hand camera for high position and pose estimation accuracy of a spatial circle. Extensive experiments are conducted to validate the effectiveness of the proposed method for position and pose estimation of circles printed on paper, real circular flat washers, and nuts.